Inhibition of nitric oxide production in RAW 264.7 cells and cytokines IL-1β in osteoarthritis rat models of 70 % ethanol extract of Arcangelisia flava (L.) merr stems - Pratama, Rizki Rahmadi; Sari, Riza Ambar; Sholikhah, Irawati; Mansor, Hakiman; Chang, Hsin-I; Sukardiman; Widyowati, Retno (Elsevier Ltd, 2024)
Introduction: One of the most frequent types of arthritis is osteoarthritis, also referred to as a degenerative joint disease. Interleukin-1β (IL-1β) and nitric oxide (NO) are essential factors in the pain response; IL-1β and NO are responsible for increasing the production of matrix metalloproteinases (MMP) and a disintegrin-like and metalloproteinases with thrombospondin motifs (ADAMS) in chondrocytes. Arcangelisia flava (L.) Merr. Has been traditionally used to treat jaundice, liver disease, diarrhea, fever, and inflammation. Methods: This study used in vitro and in vivo models to determine the effect of a 70 % ethanol extract of Arcangelisia flava (L.) Merr. stems on the inhibition of NO production in RAW 264.7 cells induced with lipopolysaccharide (LPS) and IL-1β in osteoarthritis rats induced with monosodium iodoacetate (MIA). The NO inhibition test was determined by the NO colorimetric assay using Griess reagent and measured by the ELISA plate reader. The measurement of joint diameter and hyperalgesia in osteoarthritis rats was carried out once a week for 7 weeks, and then the IL-1β levels were measured at weeks 3 and 7. Result: The viability of cell line this extract was greater than 80 %, and the extract at 25, 50, and 100 μg/mL significantly inhibited NO production (p < 0.0001) in RAW 264.7 cells induced with LPS. Meanwhile, this extract at 10, 30, and 90 mg/200g BW increased latency time, reduced joint swelling, and reduced IL-1β levels in the serum in the osteoarthritis rat model. Conclusion: 70 % ethanol extract of Arcangelisia flava (L.) Merr. Has the potential to be an anti-osteoarthritis drug.